An evaluation of the effects of budgetary process on performance of manufacturing companies: case study of Eversharp - Muzadzi, Monica P. (Midlands State University, 2015)
This research was undertaken to evaluate the effect of budgets and budgetary control on the performance of Eversharp. The main problem was that Eversharp was making losses and costs have been increasing so this research was on the background of trying to enhance the budget process and improve performance. The research goes in depth in identifying the limitations of budgeting process and its effect on performance, evaluating the current budget technique, identifying the factors both internal and external which affectthe implementing the budget process and the ways that can be implemented to improve the current budget process at Eversharp (Pvt) Ltd. This study was done using the descriptive research design using the case study technique. Stratified random sampling method was used in the selection of the sample size. Data was collected using questionnaires and one on one interviews. The collected data was presented by using charts, tables and graphs. The major findings were that the budgetary process being implemented at Eversharp has limitations and not fulfilling its desired purpose of cost reduction, minimising wastage of resources and enhancement of performance evaluation thereby resulting in losses. The recommendation were that Eversharp must integrate its budget process with strategic management and upgrade its budgetary system to the most modern software so as to improve its overall performance